A PHYSICAL ACTIVITY AND STRENGTHENING THE IMMUNE SYSTEM (Fiep Bulletin - online, 2017)
Although already known the importance of exercise for improving health, treatment of diseases and disorders, itsrelation to strengthening the immune system apparently begins in the era epidemiological chronic degenerative diseases. On thedata presented this study aims to understand what are the main benefits that physical activity practice brings to the properfunctioning of the immune system as an ally to health. This study consists of a literature integrative review in order to understandand identify the main benefits of physical activity as strengthening tool of the immune system, from literature on the topic. Thedevelopment of this integrative review started from the following question: What are the benefits that physical activity provides theimmune system as allied health? This method of study aims to gather and synthesize results of research on a limited topic orissue in a systematic and orderly manner, contributing to the deepening of knowledge of the subject investigated (SOUZA, 2010).Given the above, based on the theme: The main benefits of physical activity as a strengthening tool of the immune system. Weseek to highlight what each article brings similar and divergent for a better determination of the facts. Within this review includediscussions on hypotheses and possible suggestions, based on the findings, to improve the process. The search of the studiestook place in May 2016 and respected some of inclusion and exclusion criteria. As database was used the following sources:Virtual Health Library (VHL), database Latin American and Caribbean Health Sciences (LILACS), and the Scientific ElectronicLibrary Online (SciELO). these sources were chosen due to its credibility and quality found jobs. The selected descriptors for thesearch were: exercise, strengthening and immune system. We suggest conducting research with better control parameters inBrazil, which allow performing data intersections in subsequent ecological studies. Regarding the studies on adhesion, the mainapproach is to identify the determinants for adoption and maintenance in physical exercise, and to examine the prevalence ofphysical inactivity in the most remote regions of Brazil, confirming the known classical applications of epidemiology in the study ofdiseases in Cheers.